The effect of pH on embryonal and larval development of the Caucasian Brown Frog, Rana macrocnemis - J. M. Gamidova; A. I. Rabadanova (Юг России: экология, развитие, 2022)
Aim. To study the effect of different pH values on the characteristics of the embryonic and larval development of Rana macrocnemis.Material and methods. Fragments from 6–7 clutches of R. macrocnemis collected on the territory of Foothill Dagestan were used in the work. The experiment  included  two  series  of  experiments:  in  the  1st  series,  the entire cycle of embryonic‐larval development of the R. macrocnemis frog was  studied,  and  in  the  2nd,  only  the  postembryonic  development  of R. macrocnemis was studied. Eggs were individually placed in containers with different pH values (4.0, 5.0, and 9.0).Results.    The    most    vulnerable    periods    in    the    development    of R. macrocnemis are the stages of neurula, limb formation, and metamorphosis. At pH 4.0, oxygen consumption by larvae decreases, accompanied by suppression of feeding behavior and a decrease in the intensity of metabolic processes. In addition, pH 4.0 has a negative effect on the survival of embryos and larvae. At pH 5.0, changes are noted that are mainly of an adaptive nature. Against the background of the accelerated development of embryos at these pH values, a significant decrease  in  the  length  and  weight  of  their  body  is  noted.  With  the transition to larval development, an increase in body size is observed against the background of a small increase in weight. An elongation of the duration of the period from the beginning of the formation of limbs to the end of metamorphosis was also noted.Conclusion. The data obtained can be used in monitoring the level of acidity of the environment and the oxygen content in natural water bodies during the spawning period, which will help clarify the issue of the reduction in the number of R. macrocnemis frogs in Dagestan.